Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Hasil Belajar Matematika Siswa Kelas X MAN 1 Sleman - Esta Fania Hariani; Nanang Khuzaini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on the mathematics learning outcomes of tenth-grade students at MAN 1 Sleman and to compare its effectiveness with conventional learning. The study employed a quantitative approach using a quasi-experimental method with a Non-equivalent Control Group Design. The sample consisted of 72 students, divided into an experimental class (36 students) and a control class (36 students), selected through purposive sampling. Data were collected using a validated and reliable essay test on statistics. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired samples t-test, independent samples t-test, and Cohen's d effect size analysis. The results revealed a significant improvement in students' mathematics learning outcomes after the implementation of the CTL model. The independent samples t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the experimental and control groups. In addition, the effect size analysis produced a Cohen's d value of 0.87, which falls into the large category, indicating that the CTL model had a strong practical effect on improving students' mathematics learning outcomes. These findings suggest that the CTL model is an effective alternative learning strategy for promoting meaningful, contextual, and student-centered mathematics learning.